PENGARUH FASILITAS KANTOR TERHADAP KINERJA KARYAWAN PADA PT. BANK MANDIRI (PERSERO) Tbk. AREA MANADO - Rizaldy Dunggio; Selfy Manueke; Robby T. Mamusung (Jurusan Administrasi Bisnis Politeknik Negeri Manado, 2022)
In facing competition in the global era, companies are required to work more effectively and efficiently. The purpose of this study was to determine the effect of office facilities on employee performance at PT. Bank Mandiri (Persero) Tbk. Area Manado. The type of research is quantitative research and the research method uses descriptive research methods. Research that takes a sample from one population by using a questionnaire as a data collection tool. The population taken is the staff of employees in the division of Micro Banking Cluster 1, 2 and the division of Human Capital & General Affairs at PT. Bank Mandiri (Persero) Tbk. Area Manado. The employees in question are 78 employees but the sample involved is 37 respondents using the Simple Random Sampling method. The analysis used is Descriptive Statistical Analysis, Total Score, Simple Linear Regression Analysis and Correlation. The results of research analysis Simultaneous correlation coefficient r = 0.542 (54.2%) indicates that Office Facilities have a very strong and significant relationship to Employee Performance at PT. Bank Mandiri (Persero) Tbk. Area Manado. The coefficient of determination indicates that employee performance, 29.3% is influenced by office facilities, while the remaining 70.7% is influenced by other factors. The results of the analysis show that Office Facilities have a significant effect on increasing employee performance at PT. Bank Mandiri (Persero) Tbk. Area Manado. For this reason, office facilities need to be considered by leaders and companies by paying more attention to internal and organizational factors regarding office facilities so that they can improve employee performance